Eaten up by boredom: consuming food to escape awareness of the bored self - Moynihan, Andrew B.; Tilburg, Wijnand A. P. van; Igou, Eric R.; Wisman, Arnaud; Donnelly, Alan E.; Mulcaire, Jessie B. (Frontiers in Psychology, 2015)
Research indicates that being bored affectively marks an appraised lack of meaning in the present situation and in life. We propose that state boredom increases eating in an attempt to distract from this experience, especially among people high in objective self-awareness. Three studies were conducted to investigate boredom’s effects on eating, both naturally occurring in a diary study and manipulated in two experiments. In Study 1, a week-long diary study showed that state boredom positively predicted calorie, fat, sugar, and protein consumption. In Study 2, a high (vs. low) boredom task increased the desire to snack as opposed to eating something healthy, especially amongst those participants high in objective self-awareness. In addition, Study 3 demonstrated that among people high in objective self-awareness, high (vs. low) boredom increased the consumption of less healthy foods and the consumption of more exciting, healthy foods. However, this did not extend to unexciting, healthy food. Collectively, these novel findings signify the role of boredom in predicting maladaptive and adaptive eating behaviors as a function of the need to distant from the experience of boredom. Further, our results suggest that more exciting, healthy food serves as alternative to maladaptive consumption following boredom.